Forbidden until Midnight - Roscoe, Pippa (Harlequin presents, 2024)
New Year's Eve. It's the only day that Santo Sabatini allows his carefully controlled world to collide with heiress Eleanor Carson's. Attending the exclusive annual party he deplores is the best way the tycoon can uphold his unbreakable vow: to protect her from an earth-shattering secret...